(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
In subsequent years, many stimulants are being tested in the care of the goose, and those that have given a positive result are widely introduced into practice. The test work of such preparations as lebozol PK, Lebozol Mags SK, Lebozol potassium 450, Lebozol calcium-Forte, Lebozol Frut mix, Lebozol PK Max, Lebozol Quadro mix, Lebozol Magfos, Nutriplant 8-8-6) and Aminozol PK, whose composition is rich in micro and Macroelements, and Macroelements lebozol PK when treated with the drugs Max, lebozol magfos, nutriplant 8-8-6, lebozol boron, lebozol Mags SK, lebozol potassium 450, Lebozol Quadro mix and Aminozol, compared to the control option, a high cotton yield of 1.2-6.5 ts/Ha was achieved.